Constitutive modeling of the mechanics associated with triple shape memory polymers. (November 2015) - Moon, S.; Cui, F.; Rao, I.J.
Abstract: Shape memory polymers (SMPs) are smart materials that alter their shape in response to external stimuli. Dual-shape SMPs are widely recognized and are characterized by two shapes involved in a typical shape memory cycle. Recently, triple-shape memory polymers (TSMPs) have been introduced that have the ability to remember three shapes. Thermo-sensitive TSMPs can perform two sequential shape changes in response to heat, which were programed previously in a triple-shape creation process (TSCP). TSMPs are technologically significant as their development of has led to emergence of many complex potential applications that cannot be achieved by dual-shape polymers (Zhao et al., 2013). Crystallizable TSMPs are a class of thermo-sensitive TSMPs, where the shape creation is due to formation of crystalline phases. Different TSCPs have been reported which enable to control the triple shape capability of these materials. In this work the mechanical behavior of TSMPs has been modeled using a framework that has been developed recently for studying crystallization in polymers (Rao, 2003; Rao and Rajagopal, 2001, 2002, 2004). The framework has been used successfully to model SMPs (Barot and Rao, 2006; Barot et al., 2008), light activated SMPs (Sodhi and Rao, 2010) and is based upon the theory of multiple natural configurations. The model has been used to simulate a uni-axial deformation cycle for different types of TSCPs and the results have been compared with experimental data.